Pengaruh Penjualan, Hutang Lancar, Modal Kerja dan Perpurtaran Persediaan Terhadap Laba Bersih pada Perusahaan Industri Barang Konsumsi di Bursa Efek Indonesia Periode 2014-2018 - Nina Purnasari; Micelle Shelina; Ferdinand Lumbantobing; Erika Sirait; Jan Evanyias Pasaribu (Ekonomis: Journal of Economics and Business, 2021)
The objective of the study is to test and analyze the effect of sales, current liabilities, working capital and inventory circulation on the net profit of industry consumption goods listed in the Indonesia Stock Exchange in the period of 2014- 2018. The research used in a quantitative research approach and the nature of this research is a causal research. The research populations were all companies of industry consumption listed on the Indonesia Stock Exchange totaling 23 companies. The research sample were 115 data, drawn by purposive sampling technique. The research data were analyzed by using multiple regression analysis using F test and the T test and the coefficient of determination was obtained by the value of adjusted R Square meaning that the variations in variables of sales, current liabilities, working capital and inventory circulation, while were explained by other independent variables, by testing the classic assumption using SPSS 23. The research finding showed that partially sales, current liabilities and working capital had a significant effect on net income while inventory circulation had no effect to net income in industry consumption goods listed in the Indonesia Stock Exchange in the period 2014- 2018. Simultaneosly sales, current liabilities, working capital, inventory goods had a significant effect on net income in industry consumption goods listed in Indonesia Stock Exchange (IDX) period 2014-2018.